2015
DOI: 10.1002/acr.22490
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Disease Characteristics and Orofacial Manifestations in Systemic Sclerosis: Canadian Systemic Sclerosis Oral Health Study III

Abstract: Objective. Systemic sclerosis (SSc; scleroderma) is associated with decreased saliva production and interincisal distance, more missing teeth, and periodontal disease. We undertook this study to determine the clinical correlates of SSc with these oral abnormalities. Methods. Subjects were recruited from the Canadian Scleroderma Research Group cohort. Detailed dental and clinical examinations were performed according to standardized protocols. Associations between dental abnormalities and selected clinical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
76
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(91 citation statements)
references
References 33 publications
10
76
3
2
Order By: Relevance
“…Orofacial manifestations are commonly described among SSc patients (more than two thirds of cases) and, apparently, multifactorial [1][2][3][4][5][6]. Recent studies focused on severe impaired oral health indicating several SSc-related specific factors such as decreased oral aperture (microstomia) (43% to 80% cases) with abnormal interincisal distance (mean inter-incisal distance for people with SSc being about 33 mm), excessive dry mouth (decreased salivary flow secondary to concomitant Sjogren's syndrome) (up to 60% cases), gastroesophageal reflux disease, reduced manual dexterity (hand deformity, contractures) to maintain optimal oral hygiene, defective vascularity and alterations of the microcirculation of the gingival tissues with subsequent gingival inflammation [1][2][3][4][5][6][7][8][9]. Moreover, immunosuppressant drugs and symptomatic medication e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Orofacial manifestations are commonly described among SSc patients (more than two thirds of cases) and, apparently, multifactorial [1][2][3][4][5][6]. Recent studies focused on severe impaired oral health indicating several SSc-related specific factors such as decreased oral aperture (microstomia) (43% to 80% cases) with abnormal interincisal distance (mean inter-incisal distance for people with SSc being about 33 mm), excessive dry mouth (decreased salivary flow secondary to concomitant Sjogren's syndrome) (up to 60% cases), gastroesophageal reflux disease, reduced manual dexterity (hand deformity, contractures) to maintain optimal oral hygiene, defective vascularity and alterations of the microcirculation of the gingival tissues with subsequent gingival inflammation [1][2][3][4][5][6][7][8][9]. Moreover, immunosuppressant drugs and symptomatic medication e.g.…”
mentioning
confidence: 99%
“…It is widely accepted that dental pathology comprises more missing teeth, tooth decay and more periodontal disease in SSc as compared to age-and sex-matched healthy controls [1][2][3][4][5][6][7][8][9]. Furthermore, patients are at increased risk for dental plaque, gingival hyperplasia, gingival inflammation and, even, gingival bleeding (about 60%) [9 -11].…”
mentioning
confidence: 99%
“…6 The number of missing teeth is associated with worse hand function, the presence of GER, and decreased saliva production. 7 Oral health-related quality of life of SSc patients is significantly impaired and is not captured well by physician assessment of disease severity. 8 Use of adaptive devices such as flossers, powered oscillating-rotating toothbrushes, and orofacial exercise to improve oral health should be considered.…”
Section: Oral Cavitymentioning
confidence: 99%
“…Baron et al indicated that SSc patients have significantly worse dental health (more missing teeth, more periodontal disease) in comparison to controls. 10,44 Wood et al found that more patients with SSc presented with periodontal pockets compared to healthy controls. 45 The cause of gingivitis may be connected to the defective vascularity and changes in the microcirculation of the gingival tissues, which results in gingival bleeding.…”
Section: Scleroderma Overlap Syndromesmentioning
confidence: 99%